Oh my God - Rodger, Peter, 1965-; Hay House (Organization); Copyright Collection (Library of Congress) (Carlsbad, Calif. : Hay House, 2010)
Filmmaker Peter Rodger explores the age-old query what is God. He examines the idea of God through the minds and eyes of various religions and cultures, everyday people, spiritual leaders, and celebrities. He explores candid discussions with various Christians, Catholics, Muslims, Jews, Hindus, Buddhists and atheists from around the world.
Title from case.
Music composer, Alexander Van Bubenheim ; director of photography, Peter Rodger ; edited by John Hoyt ; executive producers, Horacio Altamirano & Metin Anter ; executive producer, Adam Krentzman.
Featuring: Hugh Jackman, Seal, Ringo Starr, Sir Bob Geldof, HRH Princess Michael of Kent, David Copperfield, Dr. John F. Demartini, Jack Thompson, and more.
DVD.
Keywords: Religions; Belief and doubt; Faith; Image of God; Fate and fatalism -- Religious aspects; Religious films; Documentary films; Nonfiction films; Feature films